Interpreting Neville - Chapman, J. Harley; Frankenberry, Nancy (State University of New York Press, 1999)
Part INeville's Methodology --Part IINeville and Western Philosophy --Part IIIMetaphysical Questions --Part IVTheological Problems --Part VComparative Issues --Part VIRobert Neville Replies --Publications of Robert Cummings Neville329.